Photocontrol of Electrical Conductance with a Nonsymmetrical Azobenzene Dithiol - Ely, Tal; Das, Sanjib; Li, Wenjie; Kundu, Pintu K.; Tirosh, Einat; Cahen, David; Vilan, Ayelet; Klajn, Rafal (Synlett, 2013)
We report a method for preparing electrode–molecule–electrode junctions that incorporate nonsymmetrical azobenzene dithiols. Our approach is based on sequential deprotection of thiol moieties originally carrying two different protecting groups. The azobenzene derivatives retained their switching properties within monolayers and permitted the photocontrol of electrical conductance.
Keywords: azo compounds; thiols; protecting groups; self-assembly; isomerization